Rapid Credit Growth in Central and Eastern Europe : Endless Boom or Early Warning? - Enoch, Charles; Otker, Inci. (Washington, D.C. : International Monetary Fund, 2007)
This volume represents the latest developments and policy debate on a very current issue: the rapid growth of banking sector credit to the private sector, which continues to occupy the minds of academics and policymakers alike in many central and eastern European (CEE) countries. The papers, presented by the representatives of international organizations and monetary and supervisory authorities of a number of western and CEE countries, provide discussions on how to assess and respond to excessive credit growth. Case studies represent the challenges faced by policymakers in dealing with rapid credit growth, providing useful lessons for other countries experiencing a similar phenomenon. For more information on how to purchase a copy of this title, please visit http://www.palgrave.com/economics/imf/index.asp.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet